2008
DOI: 10.1159/000135650
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Eicosapentaenoic Acid on Chronic Cerebral Vasospasm after Subarachnoid Hemorrhage: Possible Involvement of a Sphingosylphosphorylcholine-Rho-Kinase Pathway

Abstract: Background and Purpose: Rho-kinase (ROK)-mediated Ca2+ sensitization of vascular smooth muscle (VSM) contraction plays a pivotal role in cerebral vasospasm (CV). We previously demonstrated that sphingosylphosphorylcholine (SPC) induces Ca2+ sensitization through sequential activation of the Src family protein tyrosine kinases (Src-PTKs) and ROK in vitro, and that Ca2+ sensitization is inhibited by eicosapentaenoic acid (EPA) through the selective inactivation of Src-PTK. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 69 publications
(49 reference statements)
0
30
0
Order By: Relevance
“…ROCK inhibitors, such as fasudil have been shown to prevent cerebral vasospasm after subarachnoid hemorrhage (160,166). Similarly, animal studies showed that fasudil and Y-27632 could inhibit the development of atherosclerosis and arterial remodeling after vascular injury (183).…”
Section: Rock Inhibitors As New Therapeutics For Atherosclerosis and mentioning
confidence: 99%
“…ROCK inhibitors, such as fasudil have been shown to prevent cerebral vasospasm after subarachnoid hemorrhage (160,166). Similarly, animal studies showed that fasudil and Y-27632 could inhibit the development of atherosclerosis and arterial remodeling after vascular injury (183).…”
Section: Rock Inhibitors As New Therapeutics For Atherosclerosis and mentioning
confidence: 99%
“…In previous studies, we and others have identified the importance of assessing free fatty acid metabolism and supplementation on the occurrence of DCI. 18,42,43 Protein energy malnutrition identified in this study may be another target for intervention with amino acid supplementation. Prospective studies assessing the impact of specific amino acids and inflammation on outcome are needed to determine whether immunomodulation with nutritional supplementation may provide benefit after SAH.…”
mentioning
confidence: 90%
“…We used the method of Shirao et al 11 Briefly, adult mongrel dogs were sedated by the intraperitoneal administration of sodium pentobarbital (25 mg/kg) and allowed to breathe spontaneously. The right femoral artery was punctured percutaneously by the Seldinger technique.…”
Section: Collection Of Csf Samples After Intracisternal Spc Injectionmentioning
confidence: 99%
“…They also showed that the Rho-kinase inhibitors Y27632 and eicosapentaenoic acid (EPA) inhibited both SPC-induced vasoconstriction and CV after SAH induction. 11 Thus, we hypothesize that an increase in the concentration of SPC in cerebrospinal fluid (CSF) following SAH may mediate the SPC-Rho-kinase pathway and cause CV.…”
Section: Introductionmentioning
confidence: 99%